Tax and Overlapping Rex Sequences Do Not Confer the Distinct Transformation Tropisms of Human T-Cell Leukemia Virus Types 1 and 2 - Ye, Jianxin (American Society for Microbiology, 2003)
Human T-cell leukemia virus type 1 (HTLV-1) and HTLV-2 are distinct oncogenic retroviruses that infect several cell types but display their biological and pathogenic activity only in T cells. Previous studies have indicated that in vivo HTLV-1 has a preferential tropism for CD4(+) T cells, whereas HTLV-2 in vivo tropism is less clear but appears to favor CD8(+) T cells. Both CD4(+) and CD8(+) T cells are susceptible to HTLV-1 and HTLV-2 infection in vitro, and HTLV-1 has a preferential immortalization and transformation tropism of CD4(+) T cells, whereas HTLV-2 immortalizes and transforms primarily CD8(+) T cells. The molecular mechanism that determines this tropism of HTLV-1 and HTLV-2 has not been determined. HTLV-1 and HTLV-2 carry the tax and rex transregulatory genes in separate but partially overlapping reading frames. Since Tax has been shown to be critical for cellular transformation in vitro and interacts with numerous cellular processes, we hypothesized that the viral determinant of transformation tropism is encoded by tax. Using molecular clones of HTLV-1 (Ach) and HTLV-2 (pH6neo), we constructed recombinants in which tax and overlapping rex genes of the two viruses were exchanged. p19 Gag expression from proviral clones transfected into 293T cells indicated that both recombinants contained functional Tax and Rex but with significantly altered activity compared to the wild-type clones. Stable transfectants expressing recombinant viruses were established, irradiated, and cocultured with peripheral blood mononuclear cells. Both recombinants were competent to transform T lymphocytes with an efficiency similar to that of the parental viruses. Flow cytometry analysis indicated that HTLV-1 and HTLV-1/TR2 had a preferential tropism for CD4(+) T cells and that HTLV-2 and HTLV-2/TR1 had a preferential tropism for CD8(+) T cells. Our results indicate that tax/rex in different genetic backgrounds display altered functional activity but ultimately do not contribute to the different in vitro transformation tropisms. This first study with recombinants between HTLV-1 and HTLV-2 is the initial step in elucidating the different pathobiologies of HTLV-1 and HTLV-2.